# International Mathematical Forum, 4, 2009, no.

40, 1993 - 1995

A Note on H¨ older’s Inequality
Marwan S. Abualrub Department of Mathematics, University of Jordan P.O. Box 11942, Amman, Jordan abualrubms@yahoo.com W. T. Sulaiman Department of Mathematics, Mosul University Mosul, Iraq
Abstract In this note an easy method has been introduced to prove Holder’s Inequality.

Mathematics Subject Classiﬁcation code: 26D15 Keywords: Holder Inequality, Rogers Inequality, Cauchy Inequality, Minkowski Inequality

1

Introduction

In 1888 Rogers proved the Inequality we will be considering in this Note which has been proved later in 1889 by Holder and named after him even though some Mathematicians prefer to call it Rogers Inequality. In 1994 Hovenier [2] proved sharpening Cauchy’s Inequality; and in 1995 Abramovich, Mond, and Pecaric [1] generalized the result of Hovenier to Holder’s Inequality. Finally, it is vital to mention that Holder’s Inequality is used to prove Minkowski’s Inequality. In this Note we will give an easier proof of Holder’s Inequality.

Lemma 3. where b is ﬁxed. s 0.1 If a 0.. 2. −1 . s + t = 1. Abualrub and W. Therefore f (x) ≥ s. where 1 +1 = 1. an ) and b = (b1 . Hence F (a) ≤ 1 which gives inequality (2). 3 Main Results These are the main results of the paper.1994 M.. s Consider f (x) = x x− 1 Observe that f is decreasing with limx→1− f (x) = s. 2.. s ≺ 1. .. and in turns we have [F (a)]a=b = 1 − a + 1 = 1. where x 0. a2 . Then 1 − 1)1−s = ( 1 − 1)t . Method 2.. Method 1. In addition. s 0.. Then (2) (1 − a)s (1 − b)t ≤ 1 − as bt Proof: We will prove the above Lemma by two Methods. and t 0. S. This means that F attains its maximum at a = b. n are proportional and arg(aj bj ) is independent of j. Consider F (a) = (1 − a)s (1 − b)t + as bt . s + t = 1.. let 1 ≺ p ≺ ∞. bn ) are complex vectors. Now [F (a)]a=b = s(s − 1)[(1 − a)−1 + a−1 ] ≺ 0. and t 0. T. F (a) = 0 implies that ( a b Which gives that a = b. Sulaiman 2 Preliminary Notes We will ﬁrst consider the following Cauchy’s Inequality. b2 . . . . b ≺ 1.1 Cauchy’s Inequality Let a = (a1 . then p q n j =1 aj bj ≤ ( n j =1 |aj | ) ( p 1 p n j =1 |bj |q ) q 1 (1) In (1) equality holds if and only if the sequences {|aj |p } and {|bj |q } for j = 1...

1995 We will now proof Holder’s Inequality. S. take x = a ). 1131 . (if a b. and a ≺ b. Mond.1134. 186 (1994)..W.160. J.. 2009 . Anal. 156 . 2. 3.A note on H¨ older’s inequality b Let x = a . and Pecaric. [2] Hovenier. Appl. J. 196 (1995). Sharpening Cauchy’s Inequality. J. Sharpening Holder’s Inequality. Appl. replace a and b by 1 − a and 1 − b respectively we obtain (1 − a)s (1 − b)t ≤ s(1 − a) + t(1 − b) = 1 − sa − tb ≤ 1 − as bt . Now.2 Holder’s Inequality n−1 j =1 n−1 j =1 1 aj bj ≤ ( |aj |p ) p ( n−1 j =1 |bj |q ) q 1 (3) Proof: We want to prove that the above inequality (3) is true for j = 1.E. J. B.. Math... n. Therefore b s t a b ≤ as + bt. Math. Using the above Lemma we have n j =1 aj bj ≤ ≤ = n−1 j =1 aj bj + |an bn | 1 p p q 1 n−1 n−1 q ( j =1 |aj | ) ( j =1 |bj | ) + |an | |bn | 1 p p q q 1 n p q ( n j =1 |aj | − |an | ) ( j =1 |bj | − |bn | ) 1 p p n j =1 |aj | ) ( + |an | |bn | 1 p =( q 1 n q j =1 |bj | ) 1− ⎛ ⎜ ⎝1 − + |an | |bn | ≤( p n j =1 |aj | ) 1 p |an |p n |a |p j =1 j 1− |bn |q n |b | q j =1 j 1 q ⎞ |an ||bn | n |a |p j =1 j 1 p n |b |q j =1 j 1 q ( q n j =1 |bj | ) 1 q ⎟ ⎠ + |an | |bn | 1 p p =( n j =1 |aj | ) ( q 1 n q j =1 |bj | ) References [1] Abramovich. . Received: March. Anal..